Factors influencing intestinal anastomotic leak and their predictive value - Jina, Abhishek; Singh, Umesh Chandra (International Surgery Journal, 2019)
Background: Anastomotic leak after intestinal surgery is one of the major reasons behind postoperative morbidity and mortality. This prospective study was undertaken to evaluate various risk factors for anastomotic leakage. Methods: This study was conducted in B.R.D. Medical College, Gorakhpur, Department of surgery from May 2015 to October 2016. Patients who underwent intestinal anastomosis in emergency settings or routine operation were included in this study. Total of 156 patients were included. Results: Anastomotic leak was observed in 16.02% cases and was higher in males and in patients from low socioeconomic status. However, age, sex, and socioeconomic status were not found to be significant risk factors for anastomotic leak. Leak rate was higher in patients suffering from chronic diseases such as malignancy; COPD, DM, and patients with chronic corticosteroid use. Leak rate was significantly high in malnourished patients and in cases having sepsis as shown by their blood investigation report. After logistic regression analysis it was observe that various independent predictors for anastomotic leakages are peritonitis (p<0.05; odds ratio 2.166), bowel obstructions (p<0.05; odds ratio 2.844), blood transfusion>2 u (p<0.05; odds ratio 2.354), S. Albumin <3.0 gm/di (p<0.001; odds ratio 8.873), corticosteroid therapy (p<0.001; odds ratio 4.857), serum creatinine >1.2 mg/dl (p<0.001; odds ratio 11.755), duration of surgery (>4 hrs) (p<0.01; odds ratio 3.0251) and ASA Grading (III&IV) (p<0.01; odds ratio 3.607). Conclusions: This study has identified the potential risk factors that affect the incidence of anastomotic leakage and the result of this study will be helpful in reducing the incidence of AL after surgeries.